2020
DOI: 10.1002/mawe.201900136
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigations into microstructural and mechanical properties of as‐cast and laser powder bed fusion (LPBF) fabricated duplex steel (1.4517)

Abstract: A methodology is presented that compares the microstructural and mechanical properties of as-cast and additive-made ferritic-austenitic duplex steel 1.4517. Microstructure of approximately equal amounts of ferrite and austenite measured in as-cast material could not be replicated in post heat-treated laser powder bed fusion samples after 30 min and 60 min of post heat treatment. This is attributed to nitrogen loss during powder atomization which left fewer austenite formers. Postheat treated laser powder bed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that phases with concentrations below 5%, including chromium nitrides, micro-crystalline austenite, and process-related defects, such as pores and cracks, are identified by the EBSD detector as a fraction of zero solutions. Therefore, they are excluded from the calculation of the ferrite and austenite phase fraction [18]. The crystallographic orientation is influenced by the LPBF process parameters [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that phases with concentrations below 5%, including chromium nitrides, micro-crystalline austenite, and process-related defects, such as pores and cracks, are identified by the EBSD detector as a fraction of zero solutions. Therefore, they are excluded from the calculation of the ferrite and austenite phase fraction [18]. The crystallographic orientation is influenced by the LPBF process parameters [34].…”
Section: Discussionmentioning
confidence: 99%
“…The crystallographic orientation is influenced by the LPBF process parameters [34]. Therefore, they are excluded from the calculation of the ferrite and austenite phase fraction [18]. In this case, the DSS and SDSS process parameters of optimum samples were almost identical in terms of laser power, scan speed, and hatch distance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The corrosion resistance of the alloy system is heavily governed by the Cr, Mo, and N content [12,13]. Few studies have been conducted to establish the influence of the powder attributes and chemical composition of the starting powder on the mechanical properties and microstructure of L-PBF fabricated 25Cr7Ni stainless steel [14][15][16][17], and there has been no qualification of corrosion properties of the fabricated parts. The present study seeks to address this research gap.…”
Section: Introductionmentioning
confidence: 99%